The Position of Joint Assets Regarding the Existence of Marriage Agreements That Are Not Registered with the Dukcapil - Chaerunnisa, Chantiqa Dwi Ayudhia; Hartati, Endah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This research aims to analyze the position of joint assets in the presence of a marriage agreement that is not registered with Dukcapil after divorce based on the Marriage Law Number 1 of 1974 and the circular letter of the Ministry of Home Affairs Number 472.2/5876/DUKCAPIL in the case of decision number 2772/Pdt. G/PA CBN, namely the contents of the marriage agreement, regulates the separation of movable and immovable assets. However, the judge in his decision did not grant the request of the party who had movable assets in the marriage. This type of research is normative juridical research originating from literature studies. Regarding the results of this research analysis, namely that a marriage agreement that has never been registered with a marriage registrar cannot apply to third parties regarding the division of marital assets with a marriage agreement but remains valid between both parties. As a result, assets obtained during the marriage period are not mixed into joint assets and become the assets of each husband and wife which were acquired during the marriage. Based on the analysis that has been carried out, it is recommended that the government strengthen Article 29 paragraph 1 of the Marriage Law to state that a marriage agreement must be made in the form of a notarial deed and followed by registration with a marriage registrar so as not to raise doubts about the validity of the marriage agreement that has been made.